Development of the Ósmelur sedimentary sequence in Hvalfjörður, W-Iceland - Ríkey Júlíusdóttir 1984- (2019)
Sedimentary structures of the Ósmelur sediment formation are studied in this thesis in order to determine its formation and development. Presented are eight stratigraphical sections which were investigated with state-of-the-art field techniques, along with interpretation of aerial images, bathymetric data, radiometric datings of shells and chemical analyses of tephra. Although the Ósmelur formation represents both vertical and lateral changes in sedimentary facies, five major sedimentary units are recognized along with two glacial deposits. Radiocarbon datings on shells from the lowest and oldest unit yielded a median probability age of 14.191 cal. ka BP. Unit 2 shows signs of a regressive phase, with sandy, fluvial deposits. Unit 3 suggests climate deterioration and transgression of relative sea level, established with Unit 4, which contains radiocarbon dated shells which yielded median probability age of 13.199 cal. ka BP. Unit 5 consists of cobbles and boulders, deposited in a regressive phase in a littoral, high energy environment when isostatic rebound was occurring due to a glacier retreat. A hiatus divides Ósmelur into two parts, a table-shaped one to the west, and a terrace-shaped one to the east. This study reveals that this hiatus was caused by an erosional event, when a glacial river and a glacier from the Miðdalur valley eroded the upper/younger part of the eastern part in late Allerød or early Younger Dryas, leaving glaciofluvial sediments and a meltout till on top of it. This glacier did not reach the western formation, but a glacier from Hvalfjörður fjord reached its shoulder, leaving evidences such as diamicton and striated clasts. Setlög Ósmels voru rannsökuð til að ákvarða um uppbyggingu þeirra. Alls voru átta snið rannsökuð með klassískri aðferðafræði í feltvinnu, þar sem byggingareinkennum einstakra laga er lýst nákvæmlega. Til hliðsjónar var notast við loftmyndir af svæðinu, ásamt hafsbotnskorti, aldursákvörðuðum skeljum og efnagreindri gjósku sem fannst í tveimur sniðum. Mikill ...